Managing prevention of sexual violence and the role of commissioners in national sport federations in Germany - Hartmann-Tews, I.; Bartsch, F.; Wagner, I.; Rulofs, B. (Sport Management Review, 2020)
Many NSFs are failing to meet the general standards of child protection of the Munich Declaration of `Protection against Sexualized Violence in Sport`. The position of CPSV has a positive effect on implementing actions of prevention against sexual violence in sport. CPSV face indifference and resistance in sport organisations. Social structures of organised sport are identified that constrain and/or enable the managing of child protection with respect to the prevention of sexual violence.